The Impact of the External Environment on the Economic Security of Ukrainian Business (Economics and region, 2020)
The influence of the external environment on the economic security of business in Ukraine is studied, a number of determinants determining the content, structure and level of its provision are determined. The business environment as a complex, multidimensional, multifunctional system is considered, its features and components are defined. The determinants of the environment of direct and indirect impact on the economic security of business are characterized. It is proposed to consider the content of the concept of “economic security of a business” from the position of a functional and protective approach, taking into account the conditions of the business environment, and it allows solving fundamentally new tasks to strengthen its security and increase its ability to counteract threats and dangers at both the macro and micro levels. The goals, objects and subjects of economic security of the business, generalized organizational ways of ensuring economic security of the business from the position of a protective approach are defined. It is proved that balancing the interests of various stakeholders is an important prerequisite for the formation of a favorable business environment and economic security of the business. The main negative officials have been systematized, which will contribute to securing an economically safe business in Ukraine due to the global rating of the minds of the organization of business intelligence. The analysis of the dynamics of key indicators in the regulatory climate in Ukraine was carried out, the constructive and destructive inflow of officials of the traditional middleware to an economic safety net is marked. The authors made the evaluation the place of Ukraine and countries of the world behind the index "Doing Business-2020". Quantitative indicators are summarized that the development of the economy has been brought up, so that the economy of Ukraine is unsightly for the business, the small and medium size. It is designated that in Ukraine and in the regions there has not yet been set up a hospitable business means for securing an economically safe business, and it is designated a determinant.  The necessity of ensuring the economic security of business as a component of socio-economic development and the prerequisites for achieving the national economic interests of Ukraine is substantiated.
Keywords: economic security of the business; business environment; business climate; business conditions; determinants of economic security; threats